Data sharing scheme supporting secure outsourced computation in wireless body area network - Wei-wei ZHANG; Yu-zhao ZHANG; Chao HUANG; Ru ZHANG; Yi-xian YANG (Tongxin xuebao)
How to effectively protect the security of data sharing in WBAN was a key problem to be solved urgently.The traditional CP-ABE mechanism had a 〝one to many〝 data security communication function which was suitable for access control in WBAN,but it had high computational complexity and did not support attribute revocation.Fully considering of limitations on computation and storage of sensor nodes and dynamic user attribute in WBAN,a CP-ABE scheme was proposed which was provably secure against CPA under the standard model and supported attributes revocation,outsourced encryption and decryption.Compared with the proposed schemes,the computation burden on senor nodes is greatly reduced and the user's attribution can be revoked immediately and fine grained while meeting the demand of its security in the proposed scheme.